Modelling and Motion Analysis of a Cylindrical Steel-Rod under Very Close Distance between Electromagnets with Alternating Polarities - Hassan, Muhammad Haziq Hassani (IRC, 2020)
Electromagnetism has many properties and one of it is the electromagnetic force. Based on Coulomb’s Law, forces between electromagnets and forces between permanent magnets, the force is inversely proportional to the distance between one another. Due to this, a prototype is built by a postgraduate student which will be used to study the attraction force and response characteristics between ferrous metal and electromagnets especially at a very close distance. This is because the information for attraction force between ferrous metal and electromagnet under a very close distance is limited. Moreover, the response characteristics is yet to be known towards ferrous metal-rod.